Beyond face value the dynamics of talent-talent manager-advertising agency-client power relations in the production of shampoo and soap television commercials - Celades, Recelo G. (2012)
This study analyzes power relations that influence the employment of talents for shampoo and bath soap television commercials. It explains how power dynamics affect the behavior of the talent, talent manager, advertising agency and client in the hiring process. Intensive interviews, participant and unobtrusive observation as well as the recollection of personal experiences of 34 informants comprise the basis for the conclusion that the hierarchy of powers in the hiring process is mainly structures as Client - Advertising Agency - Talent Manager / Agency - Talent. In any of the seven arrangements of power relations analyzed in this study, the existing inequalities of these relations profit the client.
Keywords: Advertising agency and client; Talent agents; Television commercials; Television advertising